Import and export list 1963 : commodity classification and index (Lagos : Federal Ministry of Information, Printing Division, 1963)
This volume contains the official Import and Export List. The revised classification was introduced in compliance with the recommendation of the United Nations Statistical Commission that, trade-by-commodity statistics based on the Standard International Trade Classification.
lje 4/3/19
Arch
Keywords: Nigeria commerce-Nigeria.; Import and export list; Commodity and classification index; Nigeria